Exosomes from bone marrow mesenchymal stem cells protect melanocytes under vitiligo-related conditions through induction of NRF2/HO1 expression - Xuecheng Sun; Bo Huang; Gaobo Ruan; Aie Xu (PLoS ONE, 2025)
Background Vitiligo, a chronic autoimmune disease linked to excess oxidative stress, can be temporarily improved. Bone marrow mesenchymal stem cells (BMSCs)-derived exosomes (BMSCs-Exos) have recently emerged as a promising novel therapeutic means for vitiligo. Methods Exosomes were isolated and characterized from BMSCs-conditioned medium. PIG3V cells and those transfected with NRF2 siRNA or negative control were cultured under normal conditions or exposure to hydrogen peroxide (H₂O₂) to induce oxidative stress, with addition of BMSCs-conditioned medium, conditioned medium from BMSCs pretreated with GW4869 (referred to as BMSCs-GW4869), or BMSCs-Exos. Cell viability, apoptosis, and oxidative stress parameters, including cellular glutathione (GSH)/oxidized glutathione (GSSG) ratio, superoxide dismutase (SOD), reactive oxygen species (ROS), and malondialdehyde (MDA), were assessed. The expression of Ki67, NRF2, HO1, BAC, and Bcl-2 was measured. Results BMSC-Exos significantly enhanced cell viability and reduced apoptosis and oxidative stress in H₂O₂-treated PIG3V cells. Simultaneously, BMSCs-Exos reversed H₂O₂-induced downregulation of Ki67, NRF2, HO1, and Bcl-2, and upregulation of BAX in PIG3V cells. Silencing NRF2 by siRNA in PIG3V cells prior to H 2 O 2 treatment abolished the protective effect of BMSCs-Exos and decreased the HO1 expression. Conclusions BMSCs-Exos protect melanocytes from vitiliog-related oxidative stress by mitigating oxidative damage through induction of NRF2/HO1 expression.